6x-2(X+4)=4(5+x)

Simple and best practice solution for 6x-2(X+4)=4(5+x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x-2(X+4)=4(5+x) equation:


Simplifying
6x + -2(X + 4) = 4(5 + x)

Reorder the terms:
6x + -2(4 + X) = 4(5 + x)
6x + (4 * -2 + X * -2) = 4(5 + x)
6x + (-8 + -2X) = 4(5 + x)

Reorder the terms:
-8 + -2X + 6x = 4(5 + x)
-8 + -2X + 6x = (5 * 4 + x * 4)
-8 + -2X + 6x = (20 + 4x)

Solving
-8 + -2X + 6x = 20 + 4x

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '8' to each side of the equation.
-8 + -2X + 8 + 6x = 20 + 8 + 4x

Reorder the terms:
-8 + 8 + -2X + 6x = 20 + 8 + 4x

Combine like terms: -8 + 8 = 0
0 + -2X + 6x = 20 + 8 + 4x
-2X + 6x = 20 + 8 + 4x

Combine like terms: 20 + 8 = 28
-2X + 6x = 28 + 4x

Add '-6x' to each side of the equation.
-2X + 6x + -6x = 28 + 4x + -6x

Combine like terms: 6x + -6x = 0
-2X + 0 = 28 + 4x + -6x
-2X = 28 + 4x + -6x

Combine like terms: 4x + -6x = -2x
-2X = 28 + -2x

Divide each side by '-2'.
X = -14 + x

Simplifying
X = -14 + x

See similar equations:

| 3a-16=-31 | | (5y+1)(5+y)=0 | | 5x^3+2x^2=20x+8 | | 3.2s-5=5-18 | | 3x+u=7 | | 3a-16=31 | | 5(1-x)=-5(6x-6) | | 223=6*x+7 | | 12.6=x*40 | | 9(-10+x)-5(2x+9)=4-x+11 | | 5x-50=15 | | -19y=2x+.05 | | 6x+2+2-3x=-4(6x-3)+3(-x-3) | | 6a+17=-1 | | -2(2x+5)=-2+4x | | .27=x*75 | | x+.07x=15877 | | (4x+8y^2)(x-y^2)=0 | | 5h+21=11 | | W-19=6+9w | | 4(-4x+6)=-6(1+2x)-x | | X+x*4-144=0 | | -p+5=25-6p | | -5(k-3)=-90 | | 3g+17=5 | | .75*80= | | 2-x=-5(x-2) | | 4f-3=13 | | -3+2x=-(4-x) | | 2sin(x)-3=-2 | | 5d-7=23 | | 7=2x^2+6x+7 |

Equations solver categories